You need to complete the square `x^4 + 3x^2` using the formula `(a+b)^2 = a^2 + 2ab + b^2` .

`x^4 + 3x^2 = a^2 + 2ab => {(x^4 = a^2 => x^2=a),(3x^2 = 2x^2b => b = 3/2):}`

Completing the square yields:

`(x^4 + 3x^2 + 9/4) - 9/4=...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You need to complete the square `x^4 + 3x^2` using the formula `(a+b)^2 = a^2 + 2ab + b^2` .

`x^4 + 3x^2 = a^2 + 2ab => {(x^4 = a^2 => x^2=a),(3x^2 = 2x^2b => b = 3/2):}`

Completing the square yields:

`(x^4 + 3x^2 + 9/4) - 9/4= (x^2 + 3/2)^2 - 9/4`

Hence, substituting `sqrt(x^4 + 3x^2) - x^2 = sqrt((x^2 + 3/2)^2 - 9/4) - x^2 != 3/2`

**Hence, completing the square yields `(x^2 + 3/2)^2 - 9/4` , thus `sqrt(x^4 + 3x^2) - x^2 = sqrt((x^2 + 3/2)^2 - 9/4) - x^2 != 3/2.` **